WORK FAMILY CONFLICT DAN BEBAN KERJA TERHADAP STRES KERJA DIMODERASI DUKUNGAN SOSIAL PADA BANK NTB SYARIAH - Ibrahim, Isra Dewi Kuntary; Putri, Elsyah Azani; Pratama, Aryan Agus (Universitas Muhammadiyah Palembang, 2024)
Purpose - The aim of this research is test and analyse ‘The Effect of Work Family Conflict and Workload on Work Stress with Social Support Moderated at NTB Syariah Bank’. Design/methodology - The method used in this research is quantitative research. The population at Bank NTB Syariah in the officer section consists of employees with the positions of analysts, dealers, jurists, and internal control of branches with a total of 186 employees and in the staff section consists of employees with permanent employee status for customer service positions, tellers and administrative assistants, as well as outsourcing for sales funding positions, call centres, and the equivalent with a total of 492 employees and a total of 678 employees. The population in this study is 102 employees in staff and officer positions. Findings - The conclusion of this study is that work family conflict on job stress shows positive and significant results so that the hypothesis in this study is accepted. Workload on work stress shows positive and significant results so that the hypothesis in this study is accepted. Work family conflict on job stress with moderated social support shows a negative value, meaning that it can weaken or the hypothesis in this study is accepted. Workload on work stress with moderated social support shows a positive value, meaning that it cannot be able to weaken or the hypothesis in this study is rejected.